Polymerizable matrix metalloproteinases’ inhibitors with potential application for dental restorations - Laronha, Helena (2022)
Funding Information: This research was funded by A Molecular View of Dental Restoration, grant number PTDC/SAU-BMA/122444/2010 and by Molecular Design for Dental Restauration, grant number SAICT-POL/24288/2016. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.